All my rage - Tahir, Sabaa (Razorbill, 2022)
A family extending from Pakistan to California, deals with generations of young love, old regrets, and forgiveness
Keywords: Racism / Juvenile fiction; Pakistani Americans / Juvenile fiction; Families / Juvenile fiction; Immigrants / Juvenile fiction; Forgiveness / Juvenile fiction; Alcoholism / Juvenile fiction; Conflict of generations / Juvenile fiction; High school students / Juvenile fiction; Family / Juvenile fiction; California / Fiction; Family life / Fiction; Immigrants / Fiction; Forgiveness / Fiction; Racisme / Romans, nouvelles, etc. pour la jeunesse; Américains d'origine pakistanaise / Romans, nouvelles, etc. pour la jeunesse; Familles / Romans, nouvelles, etc. pour la jeunesse; Pardon / Romans, nouvelles, etc. pour la jeunesse; Alcoolisme / Romans, nouvelles, etc. pour la jeunesse; Conflit de générations / Romans, nouvelles, etc. pour la jeunesse; Élèves du secondaire / Romans, nouvelles, etc; Roman pour jeunes adultes; Californie / Romans, nouvelles, etc; YOUNG ADULT FICTION / Social Themes / Dating & Sex; YOUNG ADULT FICTION / Social Themes / Prejudice & Racism; YOUNG ADULT FICTION / Social Themes / Drugs, Alcohol, Substance Abuse; Young adult fiction; Social problem fiction; Juvenile works; Fictional Work; Fiction; Novels; Young adult works; Romans; Jugendbuch